Penggunaan Metode Pembayaran QRIS dalam Memudahkan Transaksi Jual Beli Masyarakat di Kecamatan Wangi-Wangi Menurut Ekonomi Syariah - Ogi Setiawan; La Ode Aslan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the use of QRIS (Quick Response Code Indonesian Standard) as a payment method to facilitate buying and selling transactions in Wangi-Wangi District and evaluates it from the perspective of Islamic economics. Using a qualitative approach and field research method, the researchers collected data from local stores such as Alaris, Milni Mart, and UD Mitra. The findings reveal that QRIS offers various benefits such as time efficiency, transaction security, reduced risk of counterfeit money, and ease of financial management. From an Islamic economic perspective, QRIS is considered appropriate as it promotes justice, transparency, and is free from elements of usury. Thus, QRIS is a modern solution aligned with Islamic commercial principles (muamalah), enhancing convenience and service quality in community transactions.